HUBUNGAN PERILAKU DAN PERSEPSI MAHASISWA IBM UC TERHADAP MINAT BELI PRODUK SIRSAKOE - Idelia Idelia; Cliff Kohardinata (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2016)
The purpose of this research is to investigate the purchase interest of IBM UC's students towards Sirsakoe's tea bags. Proportional Stratified Sampling is used as sampling method to select 94 respondents from a population of 1.297 students. Multiple Linear Regression analysis is used as data analysis tool with the help of SPSS 20.0. Research results indicate that the student's perception and consumer behaviour in IBM UC significantly affect the student's purchase interest in Sirsakoe's products. The coefficient of determination value in this research is 57.1. This means that 57.1% of the purchase intention is affected by consumer behaviour and perception, where as the remaining 42.9% is influenced by other factors not discussed in this study.